IMPLEMENTASI KETENTUAN PASAL 18 UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN TERKAIT PENGGUNAAN KLAUSULA EKSONERASI PADA BUKTI TRANSAKSI BARANG DI KOTA SINGARAJA - Ni Luh Eniasih; Dantes, Komang Febrinayanti; ardhya, si ngurah (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze and review the implementation of the provisions of Article 18 Paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection against the Use of Exoneration Clauses in goods businesses in Singaraja City. In practice, business actors reject the demands of consumers who experience losses due to the products they sell. The refusal of business actors is stated in the form of an exoneration clause on the proof of transaction. The type of research used in this study is empirical juridical research that is descriptive. The determination of the sample used is non-probability sampling in the form of snowball sampling. Data collection techniques are carried out by observation, interviews, questionnaires, and document studies. Based on the research conducted, it can be seen that the implementation of the provisions of Article 18 Paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection has not been effectively implemented by goods business actors in Singaraja City in Singaraja due to weak supervision carried out by legal structures and weak legal culture of the community, namely business actors and consumers related to understanding of the provisions for the use of standard clauses. The factors that cause business actors to include exoneration clauses in their transaction proofs are business actors' concerns about consumer behavior in bad faith, business policies, lack of legal awareness of business actors on the use of exoneration clauses, and the absence of socialization regarding the use of standard clauses.